The Nuances of Festive Culture: Karbi Culture and the Cultures Within (International Journal of Food and Nutritional Sciences, 2022)
The Karbis, an indigenous ethnic group primarily residing in the Karbi Anglong district of Assam, India, have a vibrant cultural heritage marked by numerous festivals and rituals. This paper is an investigation of the diverse and rich cultural practices within the Karbi community, focusing on their festive traditions. Karbi society is organized into clans, each with its own customs and rituals. The Karbi culture, like various indigenous cultures, is a dynamic culture which integrates rudiments from neighboring cultures and modern influences while preserving its core traditions. Understanding the Cultures within the Karbi festive culture involves appreciating the nuances of these practices, the symbolic meanings behind rituals, and the community's efforts to preserve their heritage in a rapidly changing world